2001
DOI: 10.1210/jcem.86.9.7850
|View full text |Cite
|
Sign up to set email alerts
|

Study of GH Sensitivity in Chilean Patients with Idiopathic Short Stature

Abstract: We hypothesized that some children with idiopathic short stature in Chile might bear heterozygous mutations of the GH receptor. We selected 26 patients (3 females, 23 males) from 112 patients who consulted for idiopathic short stature at the University of Chile. Their chronological age was 8.3 +/- 1.9, and bone age was 6.1 +/- 1.0 yr. Their height was -3.0 +/- 0.7 SDS; IGF-I, -1.2 +/- 1.1 SD; IGF binding protein 3, -0.7 +/- 2.0 SDS; and GH binding protein, 0.4 +/- 0.8 SDS. Patients were admitted, and blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 34 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…In short SGA patients, responsiveness to GH therapy varies from patient to patient, and genetic differences in the GH-IGF-I axis cascade, which leads to biological effects, have been suggested (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In two cohorts of short SGA patients, Dos Santos et al…”
Section: Discussionmentioning
confidence: 99%
“…In short SGA patients, responsiveness to GH therapy varies from patient to patient, and genetic differences in the GH-IGF-I axis cascade, which leads to biological effects, have been suggested (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In two cohorts of short SGA patients, Dos Santos et al…”
Section: Discussionmentioning
confidence: 99%
“…Our present work also demonstrated low ALS SDS (27%) and IGFBP-3 (22%) SDS values in ISS children. GHBP, IGF-I, IGFBP-3 and ALS production may be disturbed in states of GH insensitivity due to heterozygosity for specific mutations affecting the GH-IGF axis in some children with ISS [9][10][11][12][13][14]. Therefore, our results may reflect potential defects in GH receptor action that may result in partial GH insensitivity.…”
Section: Discussionmentioning
confidence: 80%
“…Abnormalities of the growth hormone-insulin-like growth factors system has been reported in ISS children [9][10][11][12][13][14][15], some of them reported in the GHR gene [9][10][11][12][13][14]. Nevertheless, the possible association of basal serum GHBP, IGF-I, IGFBP-3, and ALS with GHR-exon 3 genotype in ISS children as compared to normal children has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, all the ISS children studied have achieved a final height within their individual target height, thus confirming our biochemical diagnosis. Sjoberg et al reported an elevated GH peak frequency in 26 children (f = 3, m = 23) with ISS, whereas mean GH levels and peak amplitude were normal [16]. In 50 children with ISS, Achermann et al found an inverse relationship between GH and height velocity in 24-hour GH profiles [17].…”
Section: Discussionmentioning
confidence: 99%